Some reflections on Chomsky’s notion of reference - Enrico Cipriani (LingBaW)
In this paper, I will focus on Chomsky’s interpretation of the notion of reference. I will summarize Chomsky’s criticisms against the externalist interpretation of such notion, and I will then focus on the internalist (and syntactic) interpretation that the MIT linguist provides. Then I will focus on the relation between the internalist interpretation and the notion of truth, discussing in particular Casalegno and Hinzen’s objections: I will point out that truth does not represent a particular problem for the internalized reference. Finally, I will show how Chomsky explains, inside the internalist perspective, the phenomenon of communication. In Conclusions, I will sketch two important points.